2020
DOI: 10.1021/acsomega.0c04359
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Preparation of a H3PO4-Based Solid Catalyst for Heterogeneous Hydrolysis of Cellulose

Abstract: Cellulose saccharification to produce glucose is considered as an important approach for application of biomass resources. Solid acids as catalysts for this purpose have attracted much attention with the advantages of environmental friendliness, easy separation of products, and recyclability. In this work, a new method was introduced to prepare a H3PO4-based solid acid catalyst by simply grinding with kaolinite. Characterizations of the prepared products based on a set of analytical methods as well as cellulos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The hydrogen bond network and molecular packing impart high crystallinity in cellulosic materials, making them chemically less penetrable. Therefore, cellulose functionalization requires preactivation, either with the help of reactive chemicals (surface-modifying chemicals, such as epoxides, azides, and amines) [ 5 , 6 , 7 , 8 ] or by enforcing other energy-consuming processes (such as photoactivation, hydrothermal, thermomechanical) [ 9 , 10 , 11 , 12 , 13 ]. Due to the availability of a wide range of reactive chemical auxiliaries for cellulose material processing, various commercial-grade cellulose forms have been discovered, including nitrocellulose, sulpho-cellulose, cellulose acetate, and cellulose phosphate.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogen bond network and molecular packing impart high crystallinity in cellulosic materials, making them chemically less penetrable. Therefore, cellulose functionalization requires preactivation, either with the help of reactive chemicals (surface-modifying chemicals, such as epoxides, azides, and amines) [ 5 , 6 , 7 , 8 ] or by enforcing other energy-consuming processes (such as photoactivation, hydrothermal, thermomechanical) [ 9 , 10 , 11 , 12 , 13 ]. Due to the availability of a wide range of reactive chemical auxiliaries for cellulose material processing, various commercial-grade cellulose forms have been discovered, including nitrocellulose, sulpho-cellulose, cellulose acetate, and cellulose phosphate.…”
Section: Introductionmentioning
confidence: 99%
“…So far, different catalytic approaches to depolymerize cellulose into glucose and cello-oligosaccharides have been developed by catalysis, mechanocatalysis, and enzymolysis. Among various solid acid catalysts, zeolites are an important category owing to their low-cost, stability, and customizable architectures. The depolymerization of cellulose, a structural analogue of chitin, into glucose using silicalite-1-modified HY, HZSM-5, ,,, H-β, , H-mordenite, , H-faujasite, and SAPO-34 has been explored in recent years. Mu et al reported that the hydrolysis of cellulose is sensitive to the acid density of HZSM-5, featuring a decreasing trend with an increase of the Si/Al ratio .…”
Section: Introductionmentioning
confidence: 99%